2007
DOI: 10.1007/s00251-007-0263-1
|View full text |Cite
|
Sign up to set email alerts
|

CLEC2A: a novel, alternatively spliced and skin-associated member of the NKC-encoded AICL–CD69–LLT1 family

Abstract: The human natural killer gene complex (NKC) encodes for numerous C-type lectin-like receptors (CTLR), which are expressed on various immune cells including natural killer (NK) cells and myeloid cells. Certain activation-induced, NKC-encoded CTLR are grouped into the C-type lectin domain family 2 (CLEC2 family) which, in humans, comprises AICL (CLEC2B), CD69 (CLEC2C), and LLT1 (CLEC2D). In this paper, we characterize a novel member of the CLEC2 family, the human orphan gene CLEC2A. The C-type lectin-like domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 19 publications
5
37
0
Order By: Relevance
“…This result suggested that the 20 N-terminal aa prevented efficient production of soluble CLEC2D protein isoforms. Interestingly, a similar observation has been made for CLEC2A (11). It is therefore unlikely that a soluble LLT1 generated from alternative splicing could compete with membrane-bound LLT1.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This result suggested that the 20 N-terminal aa prevented efficient production of soluble CLEC2D protein isoforms. Interestingly, a similar observation has been made for CLEC2A (11). It is therefore unlikely that a soluble LLT1 generated from alternative splicing could compete with membrane-bound LLT1.…”
Section: Discussionsupporting
confidence: 73%
“…This vector and control RSV5-CLEC2A were generously provided by A. Steinle and described previously (11). Transient expression was obtained by electroporation of 293T and 293T-LLT1 cells (250 V, 500 microfarads).…”
Section: Cloning Of Clec2d Alternatively Spliced Transcript Variants:mentioning
confidence: 99%
“…35 It has been reported that gut-resident Th17 cells express CD161. 36 Our present study shows most decidual Th17 cells express CD161.…”
Section: Discussionmentioning
confidence: 99%
“…The cellular distribution of NKp65 receptors in vivo remains to be shown. NKp65 tightly binds to the C-type lectin-like glycoprotein KACL, which is encoded adjacently to KLRF2 in the NKC and restricted to keratinocytes (28,81). The exceptionally high affinity of the NKp65-KACL interaction (28, 82) is due to high shape complementary and a few "hotspot" amino acid residues, providing a high number of hydrogen bonds (29,82).…”
Section: Nkp65mentioning
confidence: 99%